Clinical outcomes of participants of a TB prevalence survey with an abnormal chest X-ray but no evidence of TB disease after a median follow-up of 9 months in Zambia and South Africa. - Maria Ruperez; Jacob Busang; Linda Mureithi; Kwame Shanaube; Eveline Klinkenberg; Thomas Gachie; James M Burnett; Barry Kosloff; Petra de Haas; Richard Hayes; Sarah Fidler; Ab Schaap; et al. (PLOS Global Public Health)
WHO recommends computer-aided detection (CAD) in chest X-ray (CXR) for systematic screening of TB. Increased detection of individuals with high CAD score but without bacteriologically confirmed TB can be expected, requiring guidance on their clinical management. We followed participants of a TB prevalence survey (TBPS) in Zambia and South Africa with a high CAD score but no bacteriologically confirmed TB over a median time of 9 months and assessed their clinical outcomes. At the TBPS participants with TB-suggestive symptoms or a CAD score ≥40 submitted two sputum samples for Xpert-Ultra testing, and, an additional sample was collected the next day for liquid culture and Xpert-ultra testing. Participants with a CAD score ≥70 and no bacteriologically confirmed TB were eligible for follow-up. At follow-up visit participants were asked about TB symptoms and treatment, underwent a repeat CXR with CAD, and those with either TB-suggestive symptoms or a CAD score ≥70 at follow-up submitted a sputum sample for Xpert-Ultra testing. A composite "clinical" outcome was defined based on changes in CAD-score and TB-suggestive symptoms between the TBPS and the follow-up. Of the 254 eligible TBPS participants 162 (65%) completed follow-up. Most of the participants self-reported previous TB (65% 105/162), were from Zambia (79%, 128/162,) and male (70%, 97/162). Overall, 43% (70/162) participants progressed clinically/remained radiologically abnormal and 6% (10/162) developed TB between the TBPS and the follow-up, with an overall TB incidence rate of 7% per year (95% CI: 3.8-13.3). Patients with high CAD score but no bacteriological confirmation may have had a past TB or other pulmonary lesions identified in the CXR, which may need to be investigated. Also, these participants may be at risk of progressing to TB over time and could benefit from a follow-up visit and from repeated assessment of symptoms and CXR.